Performance and suitability assessment of a real-time 3D electromagnetic needle tracking system for interstitial brachytherapy - Boutaleb, Samir; Racine, Emmanuel; Fillion, Olivier; Bonillas, Antonio; Hautvast, Gilion; Binnekamp, Dirk; Beaulieu, Luc (Journal of Contemporary Brachytherapy, 2015)
Purpose : Accurate insertion and overall needle positioning are key requirements for effective brachytherapy treatments. This work aims at demonstrating the accuracy performance and the suitability of the Aurora® V1 Planar Field Generator (PFG) electromagnetic tracking system (EMTS) for real-time treatment assistance in interstitial brachytherapy procedures. Material and methods: The system’s performance was characterized in two distinct studies. First, in an environment free of EM disturbance, the boundaries of the detection volume of the EMTS were characterized and a tracking error analysis was performed. Secondly, a distortion analysis was conducted as a means of assessing the tracking accuracy performance of the system in the presence of potential EM disturbance generated by the proximity of standard brachytherapy components. Results: The tracking accuracy experiments showed that positional errors were typically 2 ± 1 mm in a zone restricted to the first 30 cm of the detection volume. However, at the edges of the detection volume, sensor position errors of up to 16 mm were recorded. On the other hand, orientation errors remained low at ± 2º for most of the measurements. The EM distortion analysis showed that the presence of typical brachytherapy components in vicinity of the EMTS had little influence on tracking accuracy. Position errors of less than 1 mm were recorded with all components except with a metallic arm support, which induced a mean absolute error of approximately 1.4 mm when located 10 cm away from the needle sensor. Conclusions : The Aurora® V1 PFG EMTS possesses a great potential for real-time treatment assistance in general interstitial brachytherapy. In view of our experimental results, we however recommend that the needle axis remains as parallel as possible to the generator surface during treatment and that the tracking zone be restricted to the first 30 cm from the generator surface.